Safety of modified stair climbing test in the early period of rehabilitation of patients with acute myocardial infarction - D. A. Strezhneva; O. O. Knyazyuk; S. G. Kuklin; S. G. Abramovich; T. L. Amosova; E. V. Onuchina; M. V. Lukyanova (Acta Biomedica Scientifica, 2017)
Aim: safety evaluation of modified stair climbing test in the physical rehabilitation program for patients with old acute myocardial infarction. Materials and methods. Score of physical rehabilitation indices, its effectiveness and safety, comparison of physical rehabilitation indices of patients with AMI without reperfusion treatment and patients who had reperfusion interventions (bare-metal stents - in 21 persons, fibrinolysis - 1 patient, fibrinolysis and percutaneous coronary intervention - 1 patient) were estimated for 43 patients (6 women and 37 men) with old AMI using modified loading tests (stair climbing test and test with six-minute's walk). Results. HR (heart rate) fell short of submaximum values during modified stair climbing test in patient population. The condition was monitored using continuous ECG monitoring apparatus «Kardiotekhnika-04» (СС «Incart», Saint-Petersburg) None of patients showed ischemic changes of ST-segment. No significant differences were revealed in exercise tolerance between patients with old acute myocardial infarction with Q-wave who experienced stenting and patients with acute myocardial infarction without Q-wave. Results of six-minute's step test after the hospital rehabilitation stage completion show exercise tolerance increasing. Conclusion. Modified stair climbing test conducting for intensification of physical rehabilitation using subjective control was safe in examined patient population. According to six-minute's step test results, the exercise tolerance increased during rehabilitation process.